2003
DOI: 10.2165/00128071-200304040-00004
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Psychological Problems in Patients with Burn Scars

Abstract: Burn injury is often a devastating event with long-term physical and psychosocial effects. Burn scars after deep dermal injury are cosmetically disfiguring and force the scarred person to deal with an alteration in body appearance. In addition, the traumatic nature of the burn accident and the painful treatment may induce psychopathological responses. Depression and post-traumatic stress disorder (PTSD), which are prevalent in 13-23% and 13-45% of cases, respectively, have been the most common areas of researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
285
1
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(312 citation statements)
references
References 116 publications
6
285
1
11
Order By: Relevance
“…In fact, some survivors find that emotional and social adjustment to burn scarring is one of the most challenging aspects of their recovery [2,3]. Frequently experienced psychological and social problems include post-traumatic stress disorder (PTSD), major depression, substance abuse, sleep disturbance, low body image, social anxiety, stigmatization and discrimination [4][5][6][7][8][9].…”
Section: A Survey Of Burn Professionals Regarding the Mental Health Smentioning
confidence: 99%
“…In fact, some survivors find that emotional and social adjustment to burn scarring is one of the most challenging aspects of their recovery [2,3]. Frequently experienced psychological and social problems include post-traumatic stress disorder (PTSD), major depression, substance abuse, sleep disturbance, low body image, social anxiety, stigmatization and discrimination [4][5][6][7][8][9].…”
Section: A Survey Of Burn Professionals Regarding the Mental Health Smentioning
confidence: 99%
“…At the time of discharge from hospital four out of 95m patients (4%) were diagnosed with an ongoing major depression. Madianos et al (66) , face disfigurement was significantly associated with the presence of psychiatric morbidity, at least during acute hospitalization. In a review by Baur (76) comprising studies between 1986 and 1996, the prevalence rates of PTSD in adult burn populations varied between 31% and 45%.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 90%
“…Using the SCID-Imethodology, Fauerbach et al (21) reported a prevalence of 8% at discharge from hospital and 20% at the 12-month follow up. Madianor (66) who reported a prevalence rata of 18% within the 1 st month post burn and 20% at the 12-month follow-up. In a study from Tabassum Alvi et al(2009), high prevalence of depression was seen with 29 (58%) out of 50 patient and similarly high prevalence of anxiety was seen 41 (82%) patients.…”
Section: Psychiatric Manifestation In Post Burn Patientsmentioning
confidence: 98%
“…Physically, scars can impede the patient's range of motion, and can cause pain, dysesthesia and pruritus [5][6][7]. Patients with severely disfiguring scars may also experience such psychological symptoms such as low self-esteem and feelings of psychosocial isolation [8,9]. Various treatments have been developed to improve the appearance of scars and to address these adverse effects, including silicone gel sheets, pressure garments, corticosteroid therapy, dermabrasion, surgical excision, chemical peels and more recently, laser treatments [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severely disfiguring scars may also experience such psychological symptoms such as low self-esteem and feelings of psychosocial isolation [8,9]. Various treatments have been developed to improve the appearance of scars and to address these adverse effects, including silicone gel sheets, pressure garments, corticosteroid therapy, dermabrasion, surgical excision, chemical peels and more recently, laser treatments [7][8][9][10][11]. While some laser therapies have yielded positive results, others, such as the Nd: YAG and traditional ablative lasers, have actually worsened scar appearance [2,11,12].…”
Section: Introductionmentioning
confidence: 99%